Meta Analisis Pengaruh Penggunaan Bahan Ajar Terintegrasi Kearifan Lokal Terhadap Hasil Belajar Siswa - Nazifah, Naurah; Syamina, Syamina (Universitas Negeri Padang, 2021)
The development of science and technology is increasing rapidly. Improving the quality of education needs to be done as an effort to national development in the field of human resources. The government continues to improve the national education system so that it can compete with the global world. One of them is by improving the curriculum. Currently the curriculum in effect in Indonesia is the 2013 curriculum. In the 2013 curriculum, the realms of attitudes, knowledge and skills must be balanced. Therefore, new breakthroughs are needed in the world of education, one of which is integrating Indonesian local wisdom in learning. The research used is the meta-analysis method. This is in accordance with the problems and research objectives, namely to analyze the effect size on the use of integrated teaching materials integrated with local wisdom. Based on 20 journals analyzed using meta-analysis, it is known that integrated teaching materials of local wisdom are effectively used at the high school level. In addition, integrated teaching materials for local wisdom are also effective in improving student learning outcomes, and suitable teaching materials to be developed containing local wisdom are worksheets.